The impact of ownership structure on executive compensation in technology incentive and non-technology incentive companies - Farah Anisa Mohd Ghazali, author 612007; Amran Md. Ramli supervisor; Fakulti Pengurusan 538641 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Pengurusan (Teknologi) - Universiti Teknologi Malaysia, 2018